2018
DOI: 10.1097/md.0000000000010237
|View full text |Cite
|
Sign up to set email alerts
|

A 12-year analysis of closed medical malpractice claims of the Taiwan civil court

Abstract: Malpractices lawsuits cause increased physician stress and decreased career satisfaction, which might result in defensive medicine for avoiding litigation. It is, consequently, important to learn experiences from previous malpractice claims. The aim of this study was to examine the epidemiologic factors related to medical malpractice claims, identify specialties at high risk of such claims, and determine clinical which errors tend to lead to medical malpractice lawsuits, by analyzing closed malpractice claims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 28 publications
2
37
1
3
Order By: Relevance
“…10 Hwang et al found that in Taiwan, only 14.1% of verdicts in medical malpractice claims identified medical errors. 16 In Poland, a commission analysed adverse medical events and found that 23.7% of claims were due to medical errors. 19 Higher mortality but lower proportionate liability in grade-A tertiary hospitals of China In China, tertiary hospitals receive and treat mainly patients with serious diseases.…”
Section: Consistent Medical Error Risks In Grade-a Tertiary Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Hwang et al found that in Taiwan, only 14.1% of verdicts in medical malpractice claims identified medical errors. 16 In Poland, a commission analysed adverse medical events and found that 23.7% of claims were due to medical errors. 19 Higher mortality but lower proportionate liability in grade-A tertiary hospitals of China In China, tertiary hospitals receive and treat mainly patients with serious diseases.…”
Section: Consistent Medical Error Risks In Grade-a Tertiary Hospitalsmentioning
confidence: 99%
“…Thus, an analysis of completed lawsuits on medical malpractice claims could help identify priority areas where actions can reduce medical malpractice. 12 Studies of medical liability claims have directed great attention to the following topics: how to reduce medical errors [13][14][15] ; how to avoid medical damage 16 ; how to increase the ability to recognise medical malpractice 17 ; how to continuously improve the quality of medical services 18 and how to achieve satisfactory levels of patient safety. 5 19-21 On the basis of previous research, we concluded that a better understanding is needed of the relationship among adverse health outcomes, medical malpractice and patient safety.…”
mentioning
confidence: 99%
“…Lawsuits involving physicians are discussed in the literature and pointed out as one of the causes of stress, decrease of career satisfaction and exercise of defensive medicine to avoid litigious processes. (15) In addition, physicians commonly work autonomously, differentiating themselves from other health professionals who, in general, have institutional support due to the employment relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, this type of analysis has been carried out in the medical field in Taiwan, for example, where physicians also work autonomously, the average value in court convictions for medical error was around 83 thousand US dollars. (15) In Brazil, most of the time, the nursing team acts under an employment relationship with a health institution, which denotes the service of joint responsibility, for being responsible for ensuring the quality of the services offered. (4) Thus, it is justified that, from the total of civil convictions, 17 culminated in convictions of the health institution by the practice of nursing professionals, concomitantly with the manifestation of high institutional management in defense of the mistake committed by its professional (58.06%) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In medical malpractice cases insufficient and unreliable records are an important argument used by plaintiffs (Altun and Yorulmaz, 2010). For cases related to plastic surgery interventions (Vila-Nova da Silva et al, 2015;Hwang et al 2018), the main factors severely affecting court judgments were stated to be the quality of medical records and informed consent, and photographs from before and after surgery. In this research analyzing high court judgments in Turkey, the majority of interventions were surgical; however, among these there were several plastic surgery interventions and 9 (28.1%) were surgical interventions not requiring general anesthesia and medical interventions with diagnostic and/or treatment purposes.…”
Section: Discussionmentioning
confidence: 99%